Persistent increase in TNF and IL‐1 markers in severe mental disorders suggests trait‐related inflammation: a one year follow‐up study. (16th August 2017) - Mørch, R. H.; Dieset, I.; Færden, A.; Hope, S.; Aas, M.; Nerhus, M.; Gardsjord, E. S.; Haram, M.; Falk, R. S.; Joa, I.; Morken, G.; Agartz, I.; et al.
Abstract : Objective: We evaluated if plasma levels of inflammatory markers are persistently altered in severe mental disorders with psychotic symptoms or associated with state characteristics in a longitudinal study. Methods: Soluble tumor necrosis factor receptor 1 (sTNF‐R1), interleukin‐1 receptor antagonist (IL‐1Ra), von Willebrand factor (VWF), and osteoprotegerin (OPG) were measured in schizophrenia ( n = 69) and affective ( n = 55) spectrum patients at baseline and at one‐year follow‐up, and compared to healthy controls (HC) ( n = 92) with analysis of covariance. Association between change in symptoms and inflammatory markers was analyzed with mixed‐effects models. Results: sTNF‐R1 was higher in the schizophrenia ( P < 0.0001) and affective disorders ( P = 0.02) compared to HC, while IL‐1Ra was higher in schizophrenia ( P = 0.01) compared to HC at one year follow‐up. There were no significant differences between schizophrenia and affective groups; however, levels in the affective group were in between schizophrenia and HC for sTNF‐R1 and IL‐1Ra. There were no significant associations between change in symptoms and inflammatory markers. Conclusion: Persistently increased sTNF‐R1 and IL‐1Ra after one year in patients with severe mental disorders primarily reflecting data from the schizophrenia group may suggest that inflammation is a trait phenomenon, and not only the result of stress‐related mechanisms associated with acute episodes.